Collisions of monopoles, disclinations and dislocations - Pieranski, Pawel (2024)
Funding Information: M. H. G and P. P. are grateful to Arne Skjeltorp for invitation to the Geilo School 2022. The authors thank V. Klein, S. Saranga, J. Sanchez, Y. Simon, J. Saen, J.-L. Signoret and M. Bottineau for technical help. We also thank M. Zeghal, P. Judeinstein and C. Goldmann for discussions and help. Rapid progresses in experiments presented here were made during internships of M. Dazza, R. Cabeça, G. Srinivasan, J. Plo, D. Sadi, E. Thellier, T. Alezraa, A. Goré, A.Safi, R. Bouffet-Klein, B. Liagre, and N. Rouger. M.H.G. acknowledges the co-financement by FEDER, European fuand in condensed matter physicsnds, through the COMPETE 2020 POCI and PORL, National Funds through FCT Portuguese Foundation for Science and Technology and POR Lisboa2020 under projects PIDDAC (POCI-01-0145-FEDER-007688, Reference UIDB/50025/2020-2023), Action European Topology Interdisciplinary Action (EUTOPIA CA17139). Publisher Copyright: © The Author(s), under exclusive licence to EDP Sciences, Springer-Verlag GmbH Germany, part of Springer Nature 2024.